Capsulotendinous rebalancing surgery in pediatric congenital varus hallux: a case report - Meira, Gabriela Rosa; Alves do Monte, Felipe; Pastick Fujino, Rodrigo; Duarte Bezerra, Aureliano; Barbosa Silva Oliveira, Antonio Gabriel (Journal of the Foot & Ankle, 2026)
The varus hallux is characterized by medial deviation of the first toe, resulting from an imbalance between the capsuloligamentous and tendinous structures responsible for the first ray stability. The most common form is iatrogenic, usually after correction of hallux valgus; congenital presentation is rare and can occur in isolation or syndromically. Clinically, it is manifested by difficulty in wearing shoes and significant aesthetic repercussions. Surgical treatment is indicated in the face of significant deformity with functional impairment. The objective is to report capsulotendinous rebalancing surgery in a pediatric patient with non-syndromic congenital varus hallux. Case report based on review of medical records, photographic records, and outpatient follow-up in a tertiary service. The adult responsible in charge signed an Informed Consent Form. A 6-year-old male patient, with congenital varus hallux in the right foot, presents with marked medial deviation and difficulty wearing shoes. Medial longitudinal access of the hallux was performed, with medial capsulotomy, tenotomy of the abductor, and stretching of the flexors. In the first interdigital space, a V incision was made to resect the lateral capsule and the skin surplus. Immobilization with an adhesive was instituted for four weeks. In the early and late postoperative periods (2-year follow-up), the patient maintained adequate hallux alignment, wore regular shoes, and had no complications. Capsulotendinous rebalancing proved to be a safe and effective strategy for the treatment of congenital varus hallux, providing correction of misalignment, functional improvement, and adequate adaptation to footwear use. The biomechanical balance of the first ray was restored, with favorable short- and long-term evolution.